2002
DOI: 10.1111/j.1572-0241.2002.05626.x
|View full text |Cite
|
Sign up to set email alerts
|

Ureteropelvic junction obstruction: an overlooked cause of cyclic vomiting

Abstract: Cyclic vomiting syndrome is an unusual cause of recurrent episodes of repetitive vomiting, particularly in children. Although in only a minority of cases can an underlying cause be found, each patient deserves a thorough evaluation for treatable conditions. We present four cases of cyclic vomiting syndrome caused by ureteropelvic obstruction. Surgical correction was followed by resolution of symptoms in all four patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Clinicians experienced in evaluating CVS may treat without performing an extensive evaluation, but expert opinion supported performing screening tests in all children with a cyclic vomiting pattern just before administration of intravenous fluids to include electrolytes (Na + , K + , Cl − , HCO 3 − ), glucose, and upper gastrointestinal radio‐graphs to exclude malrotation (26–28). An abdominal ultrasound to rule out transient hydronephrosis, preferably during a crisis, could also be considered in refractory cases (29,30). If a patient has hyponatremia or hypoglycemia, then further evaluation should be performed to exclude Addison disease (31,32) and disorders of fatty acid oxidation (33).…”
Section: Diagnostic Approach To Recurrent Episodic Vomitingmentioning
confidence: 99%
“…Clinicians experienced in evaluating CVS may treat without performing an extensive evaluation, but expert opinion supported performing screening tests in all children with a cyclic vomiting pattern just before administration of intravenous fluids to include electrolytes (Na + , K + , Cl − , HCO 3 − ), glucose, and upper gastrointestinal radio‐graphs to exclude malrotation (26–28). An abdominal ultrasound to rule out transient hydronephrosis, preferably during a crisis, could also be considered in refractory cases (29,30). If a patient has hyponatremia or hypoglycemia, then further evaluation should be performed to exclude Addison disease (31,32) and disorders of fatty acid oxidation (33).…”
Section: Diagnostic Approach To Recurrent Episodic Vomitingmentioning
confidence: 99%
“…In 4 cases where cyclic vomiting syndrome was considered, an underlying UPJ obstruction was identified as the etiology with symptomatic imaging. 5 We strongly advocate the use of IVP in children while symptomatic for intermittent UPJ obstructions. In cases that are less clear, noncontrast computed tomography is also a viable form of imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Older children and adults typically present with intermittent abdominal pain with nausea or vomiting. 13 Schulte-Bockholt et al 14 found UPJ obstruction as the etiology in 4 cases where the working diagnosis had been cyclic vomiting syndrome. Hematuria, pyuria, hypertension, enuresis, or urinary tract infection 13 may bring some patients to a urologist for followup or result in the appropriate radiographic study from which the diagnosis is made.…”
mentioning
confidence: 98%